2016
DOI: 10.21475/ajcs.2016.10.05.p7359
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated ageing as a vigour test for crambe (Crambe abyssinica) seeds

Abstract: Adequate seed vigour tests are fundamental in evaluating vigour level and consequent performance of seed lots in storage and in the field conditions. The accelerated ageing is one of the most important of these tests. To establish the best accelerated ageing procedure for evaluating the vigour of crambe seeds, we compared results from the traditional method (ageing periods of 24, 48, and 72 hours at temperatures of 41 and 45 °C) and the saturated salt accelerated ageing (SSAA) (NaCl) method. In addition to acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
1
4
1
2
Order By: Relevance
“…Following the criterion of agility, the best option is the evaluation in the FC. These results agree with those obtained by Leão et al (2016) studying the AASS test for crambe seeds. The authors concluded that 24 h at 41 or 45 °C is best to determine vigour in this species.…”
Section: Variables Associationsupporting
confidence: 92%
See 2 more Smart Citations
“…Following the criterion of agility, the best option is the evaluation in the FC. These results agree with those obtained by Leão et al (2016) studying the AASS test for crambe seeds. The authors concluded that 24 h at 41 or 45 °C is best to determine vigour in this species.…”
Section: Variables Associationsupporting
confidence: 92%
“…For FC at 45 ºC for 48 h, the lots were classified into four vigour levels, similar to the classification found in the initial characterization. Similarly, Leão et al (2016) reported that crambe seeds should be exposed to 41 ºC for 48 h in the AA test. For Cícero cultivar, Lot 2 showed the best performance, except for FC at 41 ºC for 24 h. Lots 3 and 4 were generally classified as intermediary performances, with some differences in rank.…”
Section: Accelerated Ageing -Traditional and With Saturated Saline Somentioning
confidence: 94%
See 1 more Smart Citation
“…Standard germination tests are most widely applied to evaluate the physiological quality of seeds, but they do not provide full information about the health status of seeds and their responses to sub-optimal environmental conditions (Still, 1999). However, according to many authors, germination energy is a robust indicator of the physiological quality of crambe seeds because it describes germination rate, the first parameter that deteriorates with a decrease in seed quality (Leão et al, 2016;Taylor, 2003). In the current study, crambe seeds germinated rapidly, and germination energy was practically identical after 4 and 7 days of germination.…”
Section: Discussionmentioning
confidence: 99%
“…This technique allows investigation of morphological and structural abnormalities of the seed internal tissues and their causes (Arruda et al, 2016). The X-ray test is based on differential absorption of X-rays by the tissues; the denser and thicker the tissue, the lighter the image generated (Kotwaliwale et al, 2014). This test can be used for seeds of several species without causing damage to the seeds, as is used low doses of radiation, enabling evaluation of internal structures that otherwise would be difficult to evaluate (Xia et al, 2019).…”
Section: Introductionmentioning
confidence: 99%